Determine of Distruptive Behaviors Problems among Child Schools in Iraq - Badr, Shahznan Hassan; Lefta, Ridha. M.; AL-Talkany , Ghassan (International Journal of Psychosocial Rehabilitation, 2020)
Background: Disruptive behavior” refers to a wide range of harming acts that are seen at high rates among youth in the juvenile justice system. In fact, early psychoanalytically derived theories of delinquency posited that antisocial behavior itself was a form of destructiveness, driven by alienation, low self-regard, and perceived or actual rejection by others. Goals: To Determine of disruptive behaviors among children at primary school in Al-Najafe city; to find out the relationship between their demographic data for child school and destructive behaviors.Methodology: The study design a quantitative research by a descriptive study conducted to determine of destructive behaviors among child school in alnajafe city; to find out the relationship between their demographic data for child school and destructive behaviors. , the sampling it is non-Probability "purposive" sample was sample was conducted on 70 people with Thalassemia at the Women's and Children’s Hospital in Al-Muthanna City for the period from September 7, 2016 to February 16, 2017. A questionnaire it has used as a tool of data collection to fulfill the study, which consist of three parts, include demographic characteristics, medical history, and the health Protective behaviors. A content validity, which is carried out through 13 panel of experts. A panel of experts determines validity, while reliability use split half. A descriptive and inferential statistics are been used to analyze the data.Results: The study results indicate for demographic data that indicate the majority of the study sample for gender is male (61.3%) and age is more than 9 years within age groups (54.9%). The study results depict most of the study samples of sequences are 1-3 (68.5%) and their most have father and mother are life (93%and 93.8%) respectively. Concerned with father and mother occupation are businessman and free business respectively (46.6% and 55.1%) respectively. The study results that there is different between male and female for disruptive behaviors that indicate high significance different between male and female at p. value equal or less than 0.001.Conclusion: the study sample by their demographic data the majority of the study sample of gender is male and their age is more than 9 years within age groups. The overall assessment for distributive behaviors are their most do not suffer from distruptive behaviors after this study results are gradually elevate (mild, moderate, and sever) the distruptive behaviors among children in primary school. The study conclude that there is high a significance relationship between most of variable for demographic data and distruptive behaviors at p. value equal or less than 0.01Recommendations: Provide training session for teachers to identified distruptive behaviors, use standardized measures to help determine whether behaviours fall within the normative, borderline or at-risk, or clinically significant range. Further, scientific research that increase Screening through can complement clinical assessment when determining the need for further evaluation or intervention to prevent distruptive behaviors. Cooperation between ministry education and ministry of health to evidence-based parent-training programs as a first-line intervention for children with significant disruptive behaviors. Provide anticipatory guidance and psycho-education to parents, including directed reading, when a child’s behaviors fall within the borderline/at-risk range that lead to distruptive behaviors.